Effect of Word Card Games and Picture Cards on the Introduction of The Concept of Beginning Reading and Writing in Early Childhood (Journal of Primary Education, 2019)
The purpose of this study was to determine the effect of word card games and picture cards on the introduction of the concept of beginning reading and writing in early childhood. The type of research used in this study is experiments in the form of quasi-experimental design. The research sample was students of Kindergarten Pertiwi 1 Karangtalun, Sragen as the experimental class and Kindergarten Pertiwi 1 Kalikobok, Sragen as a control class. The data analysis technique uses the N-gain test and the independent sample t-test.The results of this study are word card game on the introduction of the concept of reading early childhood shows that the average percentage of 83% is included in very good criteria, picture card game on the introduction of the concept of reading early childhood shows that the average percentage of 76% is included in good criteria, word card game on the introduction of the concept of writing the beginning of early childhood shows an average percentage of 83% included in very good criteria, picture card game on the introduction of the concept of writing the beginning of early childhood in the experimental class shows that the average percentage of 72% is included in good criteria, there are differences in the effect of word card games and picture cards on the introduction of the concept of reading and writing beginning of early childhood students with students who do not use word card games and picture cards. Thus, it can be concluded that the word card games and picture cards game can enhance early childhood reading and writing skills.